Brassinolides have a small effect on vegetative growth, and increase reproductive growth of pistachio trees Cv. Owhadi. Issue 1 (2nd January 2019) - Pakkish, Z.; Hossien Poor, M. R.; Akbar Nasab, M. A.; Asghari, H.
ABSTRACT: The effects of different applications of 24-epi-brassinolideon the physiology and yield of 'Owhadi' pistachio trees was investigated in Iran over an off and on year. Plants were treated by 24-epi-brassinolide at 0, 0.25, 0.5, 0.75 and 1mgl −1 at green tip and tight cluster of bud stage. Brassinolide decreased the incidence nut physiological disorders and increased yield. The sprays decreased the incidence of inflorescence bud abscission, fruit abscission, misshapen nuts, blank, early splitting and indehisced shell compared with the controls. In both on and off years, the effect of brassinolide was dependent on the time of application and concentration used. Application of this compound, especially at tight cluster stage of buds, increased indehisced shell and yield in both on and off years. Brassinolides appear to play a key role in the growth and development of pistachio.